CONSIDERATION OF PANEL OF JUDGES IN THE CASE OF JOINT PROPERTY AGREEMENT TOWARDS POLYGAMOUS MARRIAGE INRELIGIOUS COURT OF CIBINONG CLASS 1B - Yunita, Gina (DERECHTSSTAAT, 2018)
A man who has more than one wife is called polygamy. A polygamy often creates legal uncertainty about joint property. The purpose of writing this thesis is to analyze the legal certainty of joint property in polygamous marriage. The research method which used in this paper is Juridical Research Methods with Sociological Approach (Empirical). Authority of the Cibinong Religious Court in examining the case of the joint treasure agreement in polygamous marriage, the Muslim husband who wishes to have more than one wife is required to apply for polygamy permission to the Religious Court under the conditions as set forth in Article 4 and Article 5 of Law Number 1 Year 1974 about Marriage. Regarding the petition for polygamy permit, it is combined with a joint property appointment request which filed by a spouse or husband who files a joint property agreement reconvention. A married husband of more than one person is governed in Article 94 of the Compilation of Islamic Law and the separation of joint property separated in the mediation room, this agreement is made or before or at the time of marriage takes place, which then authorized by religious affairs office (KUA) for Muslims and may be signed before the notary. The consideration of the Panel of Judges about the joint property agreement in polygamous marriage is seen only through evidence at that time which causing injustice to the first wife since there is no explicit lawÂ  that regulates t the distribution of joint property in polygamous marriage. Therefore, we need protection of law which is preventive and repressive